High Risk for Invasive Meningococcal Disease Among Patients Receiving Eculizumab (Soliris) Despite Receipt of Meningococcal Vaccine. Issue 9 (September 2017) - McNamara, L. A.; Topaz, N.; Wang, X.; Hariri, S.; Fox, L.; MacNeil, J. R.
Abstract : This article reviews the risk of meningococcal disease following eculizumab treatment in patients who have received the meningococcal vaccine.